Insulin release from alginate microspheres reinforced with dextran sulfate - Silva, Catarina M. (2006)
In a previous study, insulin was efficiently encapsulated in alginate microspheres using an emulsification /internal gelation process. However, these microspheres showed a high insulin release at gastric pH, exposing the protein to the harsh conditions of the stomach. In this study, our attempt was to improve insulin release profile by reinforcing the alginate matrix with dextran sulfate (DS). The size distribution was not altered by the presence of DS and the encapsulation efficiency increased to 100%. DS was also able to prevent insulin release at pH 1.2, protecting the insulin from an acidic environment. This effect was explained by an interaction between the permanent negatively charged groups of DS and insulin at low pH. When reinforced alginate microspheres were transferred to neutral pH, dissolution occurred within a few minutes. Increase of the adjuvant concentration did not improve the insulin release profile.